How do you factor -x^{2}-12x-18=0?

1 Answer
Apr 22, 2018

The solution is x=-6±3sqrt2

and hence the factorization is
(x+6-3sqrt2)(x+6+3sqrt2))=0

Explanation:

-x^2-12x-18=0
x^2+12x+18=0

Using the quadratic formula,

x= (-b+-sqrt(b^2-4ac))/(2a)

x= (-12+-sqrt(144-72))/(2 times1)

x=(-12+-sqrt72)/2

x= (-12+-6sqrt2)/2

x=-6±3sqrt2

These are the solutions when -x^2-12x-18=0

The factorization can be written in the form (x-a)(x-b) where a and b are the solutions, also known as zeros.

(x-(-6+3sqrt2))(x-(-6-3sqrt2))=0

(x+6-3sqrt2)(x+6+3sqrt2))=0